1998
DOI: 10.1080/10236249809387071
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of the burrowing behaviour ofPaphies australis(bivalvia: Mesodesmatidae)*

Abstract: Laboratory and field experiments examining the burrowing behaviour of the estuarine infaunal bivalve Paphies australis (Bivalvia: Mesodesmatidae) were conducted in two areas of northeastern New Zealand. Field experiments examining reburial showed that when exposed on the sediment surface most P. australis were able to bury within 40 min. Slightly fewer pipi buried during high-tide trials than during mid-tide trials. Laboratory experiments established the ability of P. australis of various sizes to burrow up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Juvenile mussels reportedly burrow in sediment for the first 0 to 4 yr of life after transformation (Strayer et al 2004; Schwalb *Corresponding Author: nkemble@usgs.gov and Pusch 2007; Cope et al 2008). Numerous studies have documented the burrowing behavior of older juvenile and adult mussels (Lewis and Riebel 1984;Hull et al 1998;Watters et al 2001;Archambault et al 2014;Block et al 2013;Hazelton et al 2014); they have been observed using their shell and foot to burrow into sediment. Though mussels generally are considered to be sessile, several studies have documented both vertical and horizontal movements (Kat 1982;Amyot and Downing 1991;Downing et al 1993;Balfour and Smock 1995;Amyot and Downing 1997;Schwalb and Pusch 2007;Allen and Vaughn 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile mussels reportedly burrow in sediment for the first 0 to 4 yr of life after transformation (Strayer et al 2004; Schwalb *Corresponding Author: nkemble@usgs.gov and Pusch 2007; Cope et al 2008). Numerous studies have documented the burrowing behavior of older juvenile and adult mussels (Lewis and Riebel 1984;Hull et al 1998;Watters et al 2001;Archambault et al 2014;Block et al 2013;Hazelton et al 2014); they have been observed using their shell and foot to burrow into sediment. Though mussels generally are considered to be sessile, several studies have documented both vertical and horizontal movements (Kat 1982;Amyot and Downing 1991;Downing et al 1993;Balfour and Smock 1995;Amyot and Downing 1997;Schwalb and Pusch 2007;Allen and Vaughn 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This species is endemic to New Zealand, and constitutes a thriving fisheries industry for the local market. A number of studies have been focused mainly on biological and ecological aspects of wild populations, including the reproduction and larval development (Hooker 1995), population dynamics (Hooker1995; Hewitt et al 1997;McLeod and Wing 2008), and burrowing behaviour (Hull et al 1998). While P. australis has one of the best aquaculture potentials of any New Zealand clam, there is a significant lack of information regarding its nutritional requirements and the hatchery conditions necessary for its cultivation.…”
Section: Introductionmentioning
confidence: 99%
“…The biomechanics of burrowing in bivalves have been well studied (e.g., Trueman 1983;Hull et al 1998;Tallqvist 2001) and has been shown to be influenced by factors such as substrate grain size (Lewis and Reibel 1984;De La Huz et al 2002;Candido and Romero 2007). Variation in burrowing behaviors in nature varies with season (Watters et al 2001), flow (Da Maio and Corkum 1997), and disturbance (Lewis and Reibel 1984).…”
Section: Introductionmentioning
confidence: 99%